AB0442 Long-term safety and efficacy of biosimilar infliximab (CT-P13) after switching from originator infliximab: results from the 26-week open label extension of a norwegian randomised trial. (12th June 2018) - Goll, G.L.; Jørgensen, K.K.; Sexton, J.; Olsen, I.C.; Bolstad, N.; Lorentzen, M.; Haavardsholm, E.A.; Mørk, C.; Jahnsen, J.; Kvien, T.K.; ,
Abstract : Background: The NOR-SWITCH study was funded by the Norwegian government to investigate if switching from originator infliximab (INX) to biosimilar CT-P13 is safe in rheumatoid arthritis (RA), spondyloarthritis (SpA), psoriatic arthritis (PsA), Crohn's disease (CD), ulcerative colitis (UC), and chronic plaque psoriasis (Ps). Objectives: Assessing efficacy, safety. immunogenicity at week 78 in patients on CT-P13 for 78 weeks (maintenance group) vs CT-P13 for 26 weeks (switch group). Methods: 481 adult patients on stable originator infliximab were randomised 1:1 to continued INX or switch to CT-P13 treatment in the main study 1 . All extension participants received CT-P13. The primary endpoint was disease worsening, analysed with logistic regression, adjusted for diagnosis and treatment duration. Results: 380 patients entered the extension trial. Demographic and baseline (52 w) characteristics of the extension study population are shown (table 1). Disease worsening in the study arms (Per Protocol Set, PPS) and in each diagnosis (explorative analyses) are shown (table 1). Generic disease variables, disease specific composite measures, trough drug levels, anti-drug antibodies and reported adverse events were comparable between groups (data not shown). Conclusions: We found no difference between patients switched from INX to CT-P13 vs those on maintained CT-P13 Reference: [1] Jørgensen KK, Olsen IC, Goll GL, et al. Switching from originator infliximab to biosimilar CT-P13 compared to maintained treatment with originator infliximab (NOR-SWITCH): A 52-week randomised double-blind non-inferiority trial. Lancet2017Jun 10;389(10086):2304–2316. Disclosure of Interest: G. Goll Consultant for: AbbVie, Biogen, Boehrinfer Ingelheim, Orion Pharma, Eli Lilly, Novartis, PfizerMSD, Roche, UCB, K. Jørgensen Consultant for: Tillott, Celltrion, Intercept, J. Sexton: None declared, I. Olsen Consultant for: Pfizer, N. Bolstad Consultant for: Pfizer, Orion Pharma, Napp pharmaceuticals, Takeda, M. Lorentzen: None declared, E. Haavardsholm Consultant for: AbbVie, Pfizer, MSD, Roche, UCB, C. Mørk Consultant for: AbbVie, Novartis, LEO Pharma AS, ACI hud Norge, Cellgene AS, Galderma Nordic AB, J. Jahnsen Consultant for: AbbVie, Celltrion, Takeda, Napp Pharm, AstroPharma, Hikma, Orion Pharma, Pfizer, T. Kvien Consultant for: AbbVie, Biogen, Eli Lilly, Novartis, Pfizer, MSD, Roche, UCB, Boehringer Ingelheim, Epirus, JAnssen, Merck-Serono, Mundipharma, Oktal, Orion Pharma